The Utilization of Social Media in the Classroom by Business Teacher Educators in Nigeria - James L. Morrison; Ganiiyu T. Oladunjoye; John Oyedele; Joshua Maman (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2017)
The objective of the study was to determine how frequently social media is being utilized by business teacher educators in Nigeria and for what purpose. Specifically, the research problem was to determine the kinds of pedagogical practices associated with using social media for teaching. Surveys were received from 69 business teacher educators situated in 5 states in Nigeria of which 41 were from polytechnic institutions, 22 from colleges of education, and 5 from universities. The findings indicate that social media is only being marginally implemented in business teacher education in Nigeria. However, a significant number of business teacher educators would like to see the use of social media expanded by becoming more informed as to instructional alternatives